The dynamic pattern of end-tidal carbon dioxide during cardiopulmonary resuscitation: difference between asphyxial cardiac arrest and ventricular fibrillation/pulseless ventricular tachycardia cardiac arrest - Lah, Katja (BioMed Central, 2011)
INTRODUCTION: Partial pressure of end-tidal carbon dioxide (PetCO2) during cardiopulmonary resuscitation (CPR) correlates with cardiac output and consequently has a prognostic value in CPR. In our previous study we confirmed that initial PetCO2 value was significantly higher in asphyxial arrest than in ventricular fibrillation/pulseless ventricular tachycardia (VF/VT) cardiac arrest. In this study we sought to evaluate the pattern of PetCO2 changes in cardiac arrest caused by VF/VT and asphyxial cardiac arrest in patients who were resuscitated according to new 2005 guidelines. METHODS: The study included two cohorts of patients: cardiac arrest due to asphyxia with initial rhythm asystole or pulseless electrical activity (PEA), and cardiac arrest due to arrhythmia with initial rhythm VF or pulseless VT. PetCO2 was measured for both groups immediately after intubation and repeatedly every minute, both for patients with or without return of spontaneous circulation (ROSC). We compared the dynamic pattern of PetCO2 between groups. RESULTS: Between June 2006 and June 2009 resuscitation was attempted in 325 patients and in this study we included 51 patients with asphyxial cardiac arrest and 63 patients with VF/VT cardiac arrest. The initial values of PetCO2 were significantly higher in the group with asphyxial cardiac arrest (6.74 ± 4.22 kilopascals (kPa) versus 4.51 ± 2.47 kPa; P = 0.004). In the group with asphyxial cardiac arrest, the initial values of PetCO2 did not show a significant difference when we compared patients with and without ROSC (6.96 ± 3.63 kPa versus 5.77 ± 4.64 kPa; P = 0.313). We confirmed significantly higher initial PetCO2 values for those with ROSC in the group with primary cardiac arrest (4.62 ± 2.46 kPa versus 3.29 ± 1.76 kPa; P = 0.041). A significant difference in PetCO2 values for those with and without ROSC was achieved after five minutes of CPR in both groups. In all patients with ROSC the initial PetCO2 was again higher than 1.33 kPa. CONCLUSIONS: The dynamic pattern of PetCO2 values during out-of-hospital CPR showed higher values of PetCO2 in the first two minutes of CPR in asphyxia, and a prognostic value of initial PetCO2 only in primary VF/VT cardiac arrest. A prognostic value of PetCO2 for ROSC was achieved after the fifth minute of CPR in both groups and remained present until final values. This difference seems to be a useful criterion in pre-hospital diagnostic procedures and attendance of cardiac arrest.